Empowering Santri Well-Being: Integrating Spiritual Practices and SEL in Pesantren Mental Health - Nasution, Suryadi; Jusri Pohan, Ali; Khairurrijal; Nur, Kholidah; Putriani, Zelly (IAIN Ponorogo, 2025)
This study investigates the mental health challenges faced by santri (Islamic boarding school students) in pesantren at Mandailing Natal, alongside the effectiveness of spiritual practices and Social-Emotional Learning (SEL) as coping mechanisms. Employing a mixed-methods approach, quantitative data from 200 active santri were analyzed using the Depression Anxiety Stress Scales (DASS-21), complemented by qualitative interviews with santri and ustadz (religious teachers). Findings reveal that female santri and those in grades 4–6 exhibited greater vulnerability compared to male santri and those in tsanawiyah (junior secondary) levels (p<0.05). Grade 4 marked a significant increase in mental health challenges. Salaf (traditional pesantren) reported higher anxiety levels (Mean=16.24, SD=10.87, p=0.041) compared to semi-modern institutions. Regular spiritual practices were found to reduce depression, though they proved less effective for drop-out santri facing modern pressures. SEL demonstrated potential in mitigating anxiety (OR=0.62, p=0.038, CI=0.39–0.98), with 80% of ustadz expressing support despite concerns over secularization. Integrating spirituality and SEL is recommended to holistically support santri's well-being within a modern context.